Factors affecting the development of commodity policy of the bakery industry - I. G. Chernyshova (Путеводитель предпринимателя)
The formation of an effective commodity policy is the basis for the economic success of the baking industry. Commodity policy is very important because a bread is a commodity of the first necessity and quickly loses its consumer characteristics, so it is necessary to meet the needs of customers in a timely manner and in the proper amount. The author investigates the factors influencing the formation of an effective commodity policy of the enterprises of the baking industry.